FEATURES OF CUTANEOUS MICROCIRCULATORY BLOOD FLOW IN PATIENTS WITH IDIOPATHIC PULMONARY ARTERIAL HYPERTENSION ASSESSED BY LASER DOPPLER FLOWMETRY DEPENDING ON VASOREACTIVITY STATUS ON INHALED NITRIC OXIDE - E. V. Dolgova; A. A. Fedorovich; T. V. Martynyuk; A. N. Rogoza; I. Ye. Chazova (Евразийский Кардиологический Журнал)
Aim: To evaluate features of the functional state of microvascular bed of the skin in patients with idiopathic pulmonary arterial hypertension (IPAH) depending to acute vasoreactivity testing on inhaled nitric oxide. Methods: in study included 28 patients with IPAH (mean age 39,8±13,2 years) and 25 healthy volunteers (39,3±10,1 years). All the patients underwent 6-minuts walking test (6-MWT), transthoracic echocardiography, thorax organs radiography, right heart catheterization (RHC) with acute pharmacological test (APT), laser Doppler flowmetry (LDF) with functional tests. Patients were divided into 2 groups by results of APT. Results: according to the LDF the APT+ patients didn't differ from control group on any of the parameters. The APT-patients according to the basal perfusion also were comparable with control group, but had significantly higher constrictory reactions for all types vasoconstrictor stimulations (at activation of sympathetic nervous system in respiratory and cold tests, and in the development venule-arteriolar constrictory response on venous occlusion) and elongation of time development post-occlusive reactive hyperemia. We identified significant correlation of the amplitude of respiratory section of blood flow modulation, which reflected degree of venule plethora, with the RHC parameters and functional status of patients. Conclusion: In the APT-patients on against a background the of uncharged basal perfusion parameters noticed increased constrictory activity smooth muscle cells of resistive microvessels for all type vasoconstrictor stimulations, but expression of constrictory reactions correlated with indications of patients functional status.